2022
DOI: 10.3390/insects13080727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pollen Deprivation in Groups of Tellian (Apis mellifera intermissa) and Saharan (Apis mellifera sahariensis) Honey Bees under Controlled Conditions

Abstract: Worldwide, honey bees are increasingly faced with periods of pollen scarcity, which can lead to nutritional deficiencies, especially of proteins and amino acids. These are essential for the proper functioning of the single organism and the colony. To understand how bees react to protein deficiency, under controlled conditions, we studied the effect of pollen deficiency on the main physiological parameters in two subspecies endemic of Algeria, Apis mellifera intermissa and Apismellifera sahariensis. Emerging wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Accordingly, we found that early adult life pollen deprivation for 7 days is enough to stunt honey bee survival in vitro, whereas significant impacts on longevity so far have mostly been established for life-long pollen deprivation (Omar et al, 2017;Khedidji et al, 2022) or when bees were offered only a lowered share (40%) of the amount of oilseed rape pollen usually consumed (di Pasquale et al, 2016). Consequences of early life stress in honey bees have so far been mostly investigated by manipulating parasite or nutrition levels during the developmental stages (Scofield and Mattila, 2015;Rueppel et al, 2017).…”
Section: Figurementioning
confidence: 96%
“…Accordingly, we found that early adult life pollen deprivation for 7 days is enough to stunt honey bee survival in vitro, whereas significant impacts on longevity so far have mostly been established for life-long pollen deprivation (Omar et al, 2017;Khedidji et al, 2022) or when bees were offered only a lowered share (40%) of the amount of oilseed rape pollen usually consumed (di Pasquale et al, 2016). Consequences of early life stress in honey bees have so far been mostly investigated by manipulating parasite or nutrition levels during the developmental stages (Scofield and Mattila, 2015;Rueppel et al, 2017).…”
Section: Figurementioning
confidence: 96%
“…Several molecular studies have been conducted on Algerian bees notably with microsatellite markers [ 16 ] and a single A.m. intermissa individual was sequenced [ 17 ]. In addition, research has also been performed on hive products (honey and pollen) in different scientific contexts [ 18 ].…”
Section: Introductionmentioning
confidence: 99%